Electroactive Polymer Actuators and Devices (EAPAD) XXIV 2022
DOI: 10.1117/12.2612784
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of the vibro-acoustic response in dielectric elastomer membranes

Abstract: This paper focuses on the characterisation of the vibroacoustic response of dielectric elastomer (DE) membranes. We set our attention on a circular DE membrane, deformed three-dimensionally and mounted in between fixed frames, which is able to generate sound with no need for any elastic or pneumatic biasing element. We present a finite element model of the system entirely based on commercial software Comsol Multiphysics. The model combines: 1) a mechanical model of the DE membrane, which makes use of suitably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Despite its simplicity, the system represents a suitable and simple benchmark for the parametric analyses discussed herein. The high-frequency dynamics and acoustic response of conically pre-loaded DE membranes have been investigated in our previous works [11], [13]. In particular, we observed that, upon high-frequency electrical excitation, conical DE membranes exhibit vibration mode shapes similar to those observed in flat annular tensioned membranes [14].…”
Section: System Layoutmentioning
confidence: 73%
See 4 more Smart Citations
“…Despite its simplicity, the system represents a suitable and simple benchmark for the parametric analyses discussed herein. The high-frequency dynamics and acoustic response of conically pre-loaded DE membranes have been investigated in our previous works [11], [13]. In particular, we observed that, upon high-frequency electrical excitation, conical DE membranes exhibit vibration mode shapes similar to those observed in flat annular tensioned membranes [14].…”
Section: System Layoutmentioning
confidence: 73%
“…Material dissipation is modelled via a structural damping in the frequency domain, with loss factor η d [8], [17]. Dynamics (1) and the acoustic pressure distribution p are solved for numerically using the FE model presented in [13]. The model is implemented in Comsol Multiphysics, and makes use of standard modules (Nonlinear Structural Material and Acoustics).…”
Section: Model and Validationmentioning
confidence: 99%
See 3 more Smart Citations